Longitudinal change of serum exosomal miR-186-5p estimates major adverse cardiac events in acute myocardial infarction patients receiving percutaneous coronary intervention - Ren, Lingyun; Liu, Wei; Chen, Shanshan; Zeng, Haibo (Frontiers in Cardiovascular Medicine, 2024)
Objective Our recently published study discovers that exosomal microRNA (miR)-186-5p promotes vascular smooth muscle cell viability and invasion to facilitate atherosclerosis. This research aimed to explore the prognostic implication of serum exosomal miR-186-5p in acute myocardial infarction (AMI) patients receiving percutaneous coronary intervention (PCI). Methods One hundred and fifty AMI patients receiving PCI and 50 healthy controls (HCs) were screened. Serum exosomal miR-186-5p was detected by reverse transcriptase-quantitative polymerase chain reaction assay in AMI patients at admission and after PCI, as well as in HCs after enrollment. Major adverse cardiac events (MACE) were recorded during follow-up in AMI patients receiving PCI. Results Serum exosomal miR-186-5p was raised in AMI patients vs. HCs (P < 0.001). Besides, serum exosomal miR-186-5p was positively linked to body mass index (P = 0.048), serum creatinine (P = 0.021), total cholesterol (P = 0.029), and C-reactive protein (P = 0.018); while it was reversely linked with estimated glomerular filtration rate (P = 0.023) in AMI patients. Interestingly, serum exosomal miR-186-5p was correlated with the diagnosis of ST-segment elevation myocardial infarction (P = 0.034). Notably, serum exosomal miR-186-5p was decreased after PCI vs. at admission (P < 0.001). The 6-, 12-, 18-, and 24-month accumulating MACE rates were 4.5%, 8.9%, 14.8%, and 14.8% in AMI patients. Furthermore, serum exosomal miR-186-5p ≥3.39 (maximum value in HCs) after PCI (P = 0.021) and its decrement percentage <median (35%) decrement (P = 0.044) estimated elevated MACE in AMI patients. Conclusion Serum exosomal miR-186-5p is reduced after PCI, and its post-PCI high level or minor decrease estimates increased MACE risk in AMI patients.